2019
DOI: 10.1088/1755-1315/291/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Device Selection of the Potential Wave Energy Site in Indonesian Seas

Abstract: Ocean wave energy (OWE) is one of many promising renewable energy sources with a high energy density. By using the average wave energy data of 21-year WAVEWATCH-III (WW3) model, some areas were discovered to have a great potential for the wave energy generation. This present study was evaluating the selected Wave Energy Converters (WEC) and determining their capability to do the energy capture in the potential site of the Indonesian seas. The data of WW3 indicate the energy flux of OWE in Indonesia reached to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…An application of the analysis of the wave energy resource on the Atlantic coasts and the flow behaviour within the OWC chamber was also found by means of a numerical flow simulation code [7]. Considering the above, a simple mathematical model of a wave was proposed, representing it in the form of a sinusoid, from which we will be told how much energy the converter receives [8], in addition, a dynamic modelling was presented to evaluate the electrical power in the practical use of the wave energy converter [9]; another study evaluated wave energy converters (WEC) selected and determined their ability to realize energy capture at the potential site of the Indonesian seas [10].…”
Section: Discussionmentioning
confidence: 99%
“…An application of the analysis of the wave energy resource on the Atlantic coasts and the flow behaviour within the OWC chamber was also found by means of a numerical flow simulation code [7]. Considering the above, a simple mathematical model of a wave was proposed, representing it in the form of a sinusoid, from which we will be told how much energy the converter receives [8], in addition, a dynamic modelling was presented to evaluate the electrical power in the practical use of the wave energy converter [9]; another study evaluated wave energy converters (WEC) selected and determined their ability to realize energy capture at the potential site of the Indonesian seas [10].…”
Section: Discussionmentioning
confidence: 99%
“…This reanalysis product is used to train and validate the ConvLSTM network. Usage of this product is justified as researchers have extensively validated the dataset and found that it is in good agreement with observations (Mondon and Warner, 2009;Zheng and Li, 2015;Triasdian et al, 2019). The study area is defined as the coastal waters in the northwestern Pacific Ocean enclosed by 105 • E to 126 • E and 4 • N to 43 • N. The study period is selected from 2011 to 2019.…”
Section: Significant Wave Height Reanalysis Productmentioning
confidence: 93%
“…It should be noted that not all converters require tertiary energ conversion; some only need two stages, the first and the third, to complete the entir process. [31,34,35].…”
Section: Classification and Working Principle Of Wecmentioning
confidence: 99%